AN ENTERPRENEURSHIP CURRICULUM DEVELOPMENT TO ENHANCE ENTERPRENEURSHIP COMPETENCE BASED ON COGNITIVE APPRENTICESHIP APPROACH FOR THE HIGHER VOCATIONAL CERTIFICATE STUDENTS - Tosophon, Supaporn; Kaewurai, Wareerat (Journal of Education and Innovation, 2020)
The research aimed at developing an entrepreneurship curriculum to enhance entrepreneurship competence based on cognitive apprenticeship approach for the higher vocational certificate students. The research and development (R & D) process model has been adopted to use in the study in 4 steps as follows: step 1 studying the essential entrepreneurship competences for the higher vocational certificate students, step 2 constructing an entrepreneurship curriculum to enhance entrepreneurship competence based on cognitive apprenticeship approach for the higher vocational certificate students and verifying curriculum quality, step 3 implementing an entrepreneurship curriculum to enhance entrepreneurship competence based on cognitive apprenticeship approach for the higher vocational certificate students, and step 4 evaluating an entrepreneurship curriculum to enhance entrepreneurship competence based on cognitive apprenticeship approach for the higher vocational certificate students. The experimental group was 24 higher vocation certificate students majoring in marketing and general management of Uttaradit vocational college. The research instruments consisted of entrepreneurship understanding test comprising 5 multiple choices, entrepreneurship skill evaluation form with 3 rating scales, personal characteristics evaluation form with 3 rating scales evaluated by the teacher, and learning satisfaction form. The data were analyzed by using means, standard deviations, t-test and content analysis. The results at each step were presented as follows: 1. The results of studying the essential entrepreneurship competences for the higher vocation certificate students were as follows: 1) Regarding knowledge about entrepreneurship competences consisted of entrepreneurship understanding about business and entrepreneurship, business model, management, marketing, process and production, human resources management, investment and finance, communication and business network and organizational management. Regarding entrepreneurship competences consisted of performance ability and interaction and regarding personal characteristics consisted of motivation and self-concept. 2) The teaching and learning management approach that enhances entrepreneurship. There should be learning activities by using group work to train learners to discover knowledge on their own, emphasizing hands-on activities and interesting case studies. In order for the students to see a good example, the instructor is a facilitator when the problem occurs until the learner is able to complete the task. 3) Measurement and Evaluation, It should be measured to assess the learning to cover the three aspects of knowledge with the test. Skills with skills assessment and personal qualities. 2. An entrepreneurship curriculum to enhance entrepreneurship competence based on cognitive apprenticeship approach for the higher vocational certificate students consisted of 8 components: principle and rationale, course objectives, course competence, course description, course contents, learning approaches, materials and learning resources, and evaluation. The curriculum was implemented based on cognitive apprenticeship approach for enhancing entrepreneurship competence. The teaching and learning processes consisted of 6 steps: 1) preparation, 2) modeling, 3) coaching and scaffolding, 4) Articulation, 5) though reflection, and 6) extension. The curriculum and supplementary materials were approved by the specialists and its results were at the most appropriate level. After trying out the developed curriculum, it was possible for curriculum implementation. 3. The results of implementing an entrepreneurship curriculum based on cognitive apprenticeship approach to enhance entrepreneurship competence for the higher vocation certificate students revealed that students had an entrepreneurship understanding after learning higher than before learning at .05 level of significance. Students also had entrepreneurship competence after learning higher than the criteria of 75 at .05 level of significance and had personal characteristics on entrepreneurship after learning higher than before learning at .05 level of significance. 4. The results of curriculum evaluation revealed that students had learning satisfaction toward the curriculum at high level. Regarding to the opinions of stakeholders, they viewed that the curriculum was suitable at high level in all aspects input, process and output. The curriculum has appropriate for the level of students and was developed based on relevant theory and useful for adjusting students’ prior knowledge.